Non-financial reporting by B corporations: a quest for transparency - Larroudé, Elisa Rodrigues Alves (2022)
This doctoral dissertation investigates businesses certified as B corporations (B Lab, 2018; 2019), especially their transparency, with emphasis on their published reports and how these contribute to their overall accountability. Key contributions include: a) a bespoke analytical framework, clustered into three sections: core disclosure, transversal disclosure, and transversal presentation; b) a triangulated assessment of B corporation non financial reporting, implying increased appearance of transparency may be disguising increased opacity; c) emergent analytical categories: voices (visibility, validation, volume) and silences (isolation, anonymity, invisibility); and d) proposed opacity dimensions: secrecy, misinformation, and ambiguity — supplementing Schnackenberg & Tomlinson’s (2016) transparency dimensions (disclosure, accuracy, and clarity). The literature review supporting this dissertation explores three central concepts, accompanied by related topics: (i) B corporations: contextualized within corporate social responsibility and social enterprises, (ii) accountability: overview, frameworks, and international standards, and (iii) transparency: reporting, readability, and assurance. The research employs qualitative and quantitative methodology via triangulated textual analyses: framework anchored and content, consistent with procedures proposed by Miles, Huberman & Saldaña (2014) and Neuendorf (2017), respectively. Empirical research findings on reporting by publicly traded B corporations blend main and supplemental data sources: (i) reports published by B corporations (main source), and (ii) certification impact data shared by B Lab on Data.World (2021a). Keywords: transparency, opacity, obfuscation, accountability, B corporations, non financial reporting.